ANALISIS EFEKTIVITAS PLATFORM DIGITAL DALAM MENGEMBANGKAN KETERAMPILAN PUBLIC SPEAKING DI KALANGAN MAHASISWA - Zainuddin, Zainuddin; Faiqoh, Amelia Nur; Gudsy, Silvia Harira; Wulandari, Sri (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
This study aims to analyze the effectiveness of digital platforms in enhancing public speaking skills among university students. With the rapid development of technology and the rise of online learning, digital platforms have become a primary alternative for improving public speaking abilities. Through a survey conducted with 50 students from various faculties, this research found that the majority of respondents experienced significant improvements in confidence and speaking skills after using digital platforms such as Zoom, YouTube, and Google Meet. However, some challenges were faced by a small portion of respondents, such as limited internet access and the lack of direct interaction with instructors. The findings of this study are expected to contribute to the development of digital-based curricula in higher education and provide guidance for students in choosing the right platforms for training public speaking skills.